The sustainable business strategy during the new normal era: lesson for Indonesian academic - Arief, Abdul Samad; Mulyadi, Mulyadi; Liriwati, Fahrina Yustiasari (International research journal of management, IT and social sciences, 2021)
This study examined ten sustainable business strategies that more experts have advised use running a business in the new normal era. Many findings went publication on a variety of profitable business strategies. However, very little has discussed in a balanced proportion between gaining profitable business and design with high sustainable value. Conditionally, running a business requires a variety of strategic approaches that are sustainable following the policy of the COVID-19 protocol. Understanding which strategies align with the above expectations, we have conducted a series of online literature studies using qualitative methods based on a phenomenological approach. Then, they were analyzed using the conceptual framework of higher education research skills. Through this process, the authors ensured that these findings are valid and reliable. Finally, we summarized ten relevant, sustainable business strategies that are relevant to be applied in the new normal business era in Indonesia. They include continuity strategy, business to business, opportunity strategy, rethinking, lesson learned strategies, working from home, affected policies, new thinking patterns, flexibility strategies, and understanding of new processes. Therefore, these findings will provide profound insight for business people and academicians to work on business practices' sustainability to facing the pandemic disruption.